Steamboats CHAS. H. HAMILTON and COLUMBIAN discharging cargo at a boat landing in Dawson, Yukon Territory, approximately 1899. - Hegg, Eric A., 1867-1948 (1899)
Caption on image: "Discharging cargo at Dawson City"